2017
DOI: 10.1016/j.ejps.2017.09.018
|View full text |Cite
|
Sign up to set email alerts
|

Provoking an end-to-end continuous direct compression line with raw materials prone to segregation

Abstract: Continuous manufacturing of solid oral dosage forms is promising for increasing the efficiency and quality of pharmaceutical production and products. In this study a whole train continuous direct compression (CDC) line has been provoked using challenging formulations typically prone to segregation in batch powder processing. Industrial compositions including components with variable size, bulk density and cohesive nature were selected. An experimental design, including variables such as API/mannitol particle s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 38 publications
3
27
0
Order By: Relevance
“…With respect to the feeder data, the variation was different with both APIs, but in all cases, variations were such that the mixer could smoothen out the variations as the tablets passed the final content uniformity test. This is in good accordance with the results already presented for mixer smoothing of brief variations in feeding [29,43,44,50]. One limitation in this study was the mixer used, as it is working basically all the time in the fluidized mixing mode (i.e., a high Fr number) limiting the possibility of comprehensively demonstrating the effect of mixing parameters on end product quality.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…With respect to the feeder data, the variation was different with both APIs, but in all cases, variations were such that the mixer could smoothen out the variations as the tablets passed the final content uniformity test. This is in good accordance with the results already presented for mixer smoothing of brief variations in feeding [29,43,44,50]. One limitation in this study was the mixer used, as it is working basically all the time in the fluidized mixing mode (i.e., a high Fr number) limiting the possibility of comprehensively demonstrating the effect of mixing parameters on end product quality.…”
Section: Discussionsupporting
confidence: 90%
“…If one wishes to find a balance between sufficient flow properties for API and excipients and blend homogeneity, it is important to appreciate how different parameters affect the processability. Consequently, studies have been published describing the effect of raw material properties on mixing behavior [19][20][21]33,[38][39][40]; furthermore, the interaction between material properties and process parameters with different types of continuous manufacturing set-ups has been discussed [22,24,29,33,[40][41][42][43][44]. However, as far as we are aware, the number of studies where both a constant excipient formulation and excipient/API relation have been examined in a CDC process is very limited.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies investigating continuous mixing have noted that commonly used continuous mixers are very capable of handling mixtures with a segregation tendency (Oka et al, 2017;Pawar et al, 2016;Vanarase et al, 2013;Vanarase and Muzzio, 2011;Van Snick et al, 2017b). In addition, for more realistic industrial compositions, prone to segregation in batch manufacture, CDC was found notably advantageous (Lakio et al, 2017). However, it was also concluded that the quality of the end-product was largely dependent on the material properties.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…A few continuously manufactured products have already received approval by the regulatory authorities, which further confirms the applicability of this technology and explains the desire of the companies to adopt this approach (Almaya et al, 2017;Brennan, 2016;DiProspero, 2018;PharmTech, 2018). The most straightforward manufacturing process for tablets is direct compression, and the ability to couple continuous mixing to tableting, which is inherently continuous in its nature, has already been demonstrated in several studies (Engisch and Muzzio, 2016;Ervasti et al, 2015;Lakio et al, 2017, 2016, Van Snick et al, 2017a, 2017b. With integrated continuous mixing followed by direct compression, one can avoid several unit operations, such as the steps related to granulation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation